Analisis Implikasi Kepuasan Pelanggan Terhadap Perilaku Pasca Pembelian Melalui Testimoni Dalam Situs Pemasaran Internet - Nanis Susanti (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2009)
In global market area, not only marketing concept we have to do, but also applied marketing technology. Getting the service quality is doing by not only physical meet among the customer and service provider, such as conventional market system. In modern community there are like to be faster and instant, time limited is the reason for customer to shopping in the recent system. By the modern marketing system with applying internet technology, called Internet marketing, the time constraint be minimized. The modern marketing system will closer the distance within the customer and department store, nevertheless just in home shopping. A satisfied customer wills recommend their experience to their community, in either on line community or face to face. Studying and analyzing online store network Zappos.com generate the importance factors for customer satisfaction that will be impact to post purchase behavior. Descriptive analysis using data base of testimony have been explore, there are importance factors: product quality, service quality. That mean testimony is guidance to the other online store how hearing the voice of customer.